The Influence of Attitudes and Beliefs on the Problem-Solving Performance - Sturm, Nina; Bohndick, Carla (Frontiers in Education, 2021)
The problem-solving skills of primary school students depend on their attitudes and beliefs. As it is not easy to change attitudes, we aimed to change the relationship between problem-solving skills and attitudes with a training program. The training was based on the assumption that self-generated external representations support the problem-solving process. Furthermore, we assumed that students who are encouraged to generate representations will be successful, especially when they analyze and reflect on their products. A paper-pencil test of attitudes and beliefs was used to measure the constructs of willingness, perseverance, and self-confidence. We predicted that participation in the training program would attenuate the relationship between attitudes and problem-solving skills and that non-participation would not affect the relationship.